2023
DOI: 10.1523/jneurosci.0228-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Transcranial Magnetic Stimulation and Loud Sounds Produces Plastic Changes in Motor Output

Abstract: Most current methods for neuromodulation target the cortex. Approaches for inducing plasticity in sub-cortical motor pathways such as the reticulospinal tract could help to boost recovery after damage (e.g. stroke). In this study, we paired loud acoustic stimulation (LAS) with transcranial magnetic stimulation (TMS) over the motor cortex in male and female healthy humans. LAS activates the reticular formation; TMS activates descending systems, including corticoreticular fibers. Two hundred paired stimuli were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Several facts speak against a cortical influence on the coupling‐like response: first, LAS‐related effects seem to be weak during muscle contraction (Chen et al., 2016). Second, a relevant cortical suppression at 50 ms after LAS (Furubayashi et al., 2000; Tazoe & Perez, 2017; Germann et al., 2023) should modulate the coupling‐like response without startle, but not the shifted one with startles. Third, the similarity of the responses to LAS and ES makes a LAS‐induced cortical extra‐effect implausible.…”
Section: Discussionmentioning
confidence: 99%
“…Several facts speak against a cortical influence on the coupling‐like response: first, LAS‐related effects seem to be weak during muscle contraction (Chen et al., 2016). Second, a relevant cortical suppression at 50 ms after LAS (Furubayashi et al., 2000; Tazoe & Perez, 2017; Germann et al., 2023) should modulate the coupling‐like response without startle, but not the shifted one with startles. Third, the similarity of the responses to LAS and ES makes a LAS‐induced cortical extra‐effect implausible.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results were in keeping with other studies demonstrating shortening in movement onset in both the arm and the trunk during forward reaching (Yang et al., 2019 ) and rapid unilateral shoulder flexion (Tsao et al., 2009 ). It is suggested that the shortening in motor response is due to engagement of subcortical structures such as the reticular formation, which mediates spinal interneurons and motoneurons via the reticulospinal tract and thereby influences spinal excitability (Carlsen & Maslovat, 2019 ; Germann et al., 2023 ; Yeomans & Frankland, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the acoustic startle response, an unexpected acoustic stimulus is delivered, and electromyography (EMG) is recorded from proximal upper extremity muscles to quantify drive from the reticulospinal system ( 99 ). The technique has been successfully used in animal models ( 100 103 ) and clinical ( 104 106 ) studies to identify the involvement of reticulospinal pathways. Using the startle response, it has been suggested that reticulospinal pathways are involved in spasticity ( 107 ) and have enhanced function in severely impaired patients ( 75 ); although contradictory findings have also been reported ( 108 , 109 ).…”
Section: Electrophysiology Methods To Understand Alternative Motor Pa...mentioning
confidence: 99%